Incidence and outcomes of in-hospital resuscitation for cardiac arrest among paediatric patients in Jordan: a retrospective observational study - Ahmad Alrawashdeh; Zaid I Alkhatib (BMJ Paediatrics Open)
Objective To investigate the incidence and survival rates of paediatric patients receiving resuscitation for in-hospital cardiac arrest (IHCA) in a teaching hospital in Northern Jordan, comparing initial pulseless rhythms and bradycardia rhythm with poor perfusion.Design Retrospective observational studySetting An university-affiliated tertiary hospital in Northern Jordan, covering January 2015 to December 2022.Patients All hospitalised paediatric patients aged 1 month–18 years who received cardiopulmonary resuscitation (CPR) for cardiac arrest were included in the study. Resuscitation attempts were categorised into initial pulseless rhythm events and bradycardia with poor perfusion events.Main outcome measures Incidence rate of paediatric CPR and the survival to hospital discharge rate.Results A total of 504 paediatric patients received CPR during the study period, with an incidence rate of 6.26 per 1000 paediatric admissions. The annual incidence rate was significantly reduced by an average of 5.5% for the total sample but increased by 25.0% for bradycardia events (n=110, 21.8%). The percentage of patients who sustained return of spontaneous circulation (ROSC) was 25.0%. Survival to hospital discharge was low at 4.8% while showing an increasing trend by an average of 24.0% per year. Bradycardia events had a significantly higher ROSC rate (34.6% vs 22.3%); but an insignificant higher survival rate (6.4 vs 4.3). Patients with neurological or cardiovascular medical conditions, those in non-intensive care unit departments, and those with respiratory causes had higher odds of survival to discharge.Conclusion While the incidence rate of paediatric IHCA in Jordan is comparable to developed countries, the survival rate is much poorer. The study highlights the importance of strengthening healthcare infrastructure, establishing national legal and ethical frameworks around resuscitation policies and establishing robust data registries to monitor and optimise care practices.